Prevailingperceptions aboutpeople's participation in disaster management in two barangays in Metro Manila. - Tojos, Leticia S. (2012)
This study was an attempt to look into how barangay officials continuously engaged the residents in DRRM activities in Santolan, Pasig and Tumana, Marikina. Using various data gathering methodologies, one area explored was the perceived notions of the local government department heads, members of the local disaster coordinating council, non-government and people's organization representatives (key informants) and those of the residents vis-a-vis the prespective about community participation promoted by the research team.

The data generated from the nineteen key informants and one hundred purposively chosen dwellers would provide valuable learnings not only to local officials but also to development planners and practitioners. It would enhance their understanding about the the many facets of eliciting and sustaining the residents' active involvement in disaster risk reduction and management at the barangay level. As was earlier mentioned, the results might impact in reducing disaster risks and minimizing the costs of destruction in the localities.
Keywords: Emergency management -- Tumana (Marikina); Emergency management -- Santolan (Pasig); Disaster relief -- Citizen participation -- Tumana (Marikina); Disaster relief -- Citizen participation -- Santolan (Pasig)